High‐level βIII‐tubulin overexpression occurs in most head and neck cancers but is unrelated to clinical outcome. (9th July 2017) - Nienstedt, Julie C.; Gröbe, Alexander; Clauditz, Till; Simon, Ronald; Muenscher, Adrian; Knecht, Rainald; Sauter, Guido; Moebius, Christoph; Blessmann, Marco; Heiland, Max; Pflug, Christina
Abstract : Background: βIII‐tubulin (TUBB3) is an isotype of microtubules, which are involved in crucial cellular roles including maintenance of cell shape, intracellular transport, and mitosis. Overexpression of TUBB3 was found to be associated with poor prognosis and resistance to tubulin‐binding drugs and in several solid tumors including head and neck squamous cell carcinomas (HNSCC). Considering the potential high importance of a prognostic biomarker in these cancers, this study aimed to investigate the clinical relevance of immunohistochemical TUBB3 expression in HNSCC. Methods: Tissue microarray (TMA) sections containing samples from 667 cancers of oral cavity, oro‐ and hypopharynx, and larynx for which follow‐up data were available were analyzed for TUBB3 expression by immunohistochemistry. Results: Over 90% of our analyzed cancers showed unequivocal cytoplasmic TUBB3 expression. Staining was considered weak in 69 (15.5%), moderate in 149 (33.5%), and strong in 188 (42.2%) of cancers. The frequent TUBB3 overexpression showed no significant correlation with pathological grading, tumor stage, nodal status, or surgical margin and had no impact on patient outcomes. Conclusion: Despite lacking prognostic utility in HNSCC, the remarkable high prevalence of TUBB3 expression in HNSCC emphasizes its putative relevance as a target for future drugs targeting TUBB3.